2016
DOI: 10.1074/jbc.m115.683656
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobiales-like Phosphatase 2 from Arabidopsis thaliana Is a Novel Phospho-tyrosine-specific Phospho-protein Phosphatase (PPP) Family Protein Phosphatase

Abstract: Cellular signaling through protein tyrosine phosphorylation is well established in mammalian cells. Although lacking the classic tyrosine kinases present in humans, plants have a tyrosine phospho-proteome that rivals human cells. Here we report a novel plant tyrosine phosphatase from Arabidopsis thaliana (AtRLPH2) that, surprisingly, has the sequence hallmarks of a phospho-serine/threonine phosphatase belonging to the PPP family. Rhizobiales/Rhodobacterales/Rhodospirillaceae-like phosphatases (RLPHs) are conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…AtMIA40 immunoprecipitation was performed with 50 mg protein extract isolated from 10-d-old dark-grown Arabidopsis cell culture as in Uhrig et al (2016). Protein extract was pretreated with 20 mM DTT for 45 min at 4°C followed by alkylation with 110 mM NEM for 1 h at 4°C.…”
Section: Atmia40 Immunoprecipitationmentioning
confidence: 99%
“…AtMIA40 immunoprecipitation was performed with 50 mg protein extract isolated from 10-d-old dark-grown Arabidopsis cell culture as in Uhrig et al (2016). Protein extract was pretreated with 20 mM DTT for 45 min at 4°C followed by alkylation with 110 mM NEM for 1 h at 4°C.…”
Section: Atmia40 Immunoprecipitationmentioning
confidence: 99%
“…The substrate specificity of the RLPH2 enzyme from Arabidopsis was previously defined through a biochemical approach and found to be highly specific for phosphotyrosine, although the sequence of the enzyme revealed a catalytic core that is characteristic of the PPP family (8,10). In addition, AtRLPH2 was found to be sensitive to the tyrosine phosphatase inhibitor vanadate, which typically does not affect the activities of PPP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that AtRLPH2 displays a clear preference for substrates containing phosphotyrosine compared to substrates containing phosphoserine or phosphothreonine (10). Upon exploring additional peptides as substrates, we discovered that AtRLPH2 readily dephosphorylated peptides derived from mammalian mitogen-activated protein kinases (MAPKs) within their dual phosphorylated pTxpY activation loops and these were some of the best substrate peptides we identified.…”
Section: Recognition Of Tyrosine-phosphorylated and Dual Threonine-anmentioning
confidence: 93%
See 2 more Smart Citations